Non-ohmic conduction in tin dioxide based ceramics with copper addition - Gaponov, A.V.; Glot, A.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The current-voltage characteristics and temperature dependences of electrical conductivity in SnO₂-Co₃O₄-Nb₂O₅-Cr₂O₃-CuO semiconductor ceramics are studied, and possible mechanism of non-ohmic conduction in these materials is discussed. Due to addition of CuO up to 0.5 mol.%, the nonlinearity coefficient is increased up to 75, and the electric field is decreased down to 3900 V∙cm¹ (at 1 mA∙cm⁻²). It makes CuO addition useful for the preparation of SnO₂-based varistors. It is concluded that the electrical conduction is controlled by grain-boundary barriers. The activation energy of electrical conduction (the barrier height φ) is decreased with an increase in the electric field E. The higher slope of the dependence at high fields can be related to a participation of minority carriers (holes). The addition of more than 0.5 mol.% CuO leads to degradation of the varistor effect due to percolation via quite conductive CuO-based intergranular phase.